A Study on the Protection Strategies of Historical Buildings in Longshengzhuang Commercial Area, Inner Mongolia, Based on Comprehensive Value Grading - Guo, Xiaohong; Jia, Wenliang; Guo, Lijuan (International Journal of Multidisciplinary Research, 2026)
Commercial historical buildings, as products of the fusion of commercial activities and historical culture, possess unique architectural styles and profound historical connotations. They are not only a key component of cultural heritage but also witnesses to urban history and culture. This paper takes the historical buildings of Longshengzhuang Commercial Area as its research object, constructing a comprehensive value evaluation system for these buildings based on seven indicators: historical value, scientific value, artistic value, commercial value, social value, surrounding spatial environment, and surrounding cultural environment. The system evaluates and delineates the protection levels of the Longshengzhuang Commercial Area historical buildings, proposing graded protection measures from three dimensions: overall protection strategy, protection objectives, and specific measures.